1967
DOI: 10.1002/zaac.19673500309
|View full text |Cite
|
Sign up to set email alerts
|

Zur Chemie und Konstitution borsaurer Salze. XVI. Über die Hydrate des Magnesium(1:3)‐borates, MgB6O10 · x H2O

Abstract: Mit steigender Konzentration der Komponenten MgO und H3BO3 treten relativ unabhängig von der Temperatur bei B/Mg · 6 nacheinander die Hydrate MgB6O10 · 7,5 H2O, MgB6O10 · 7 H2O, MgB6O10 · 6 H2O und MgB6O10 · 5 H2O im System MgOB2O3H2O auf. Die gleichen Substanzen sind auch im System MgOB2O3H2OMgCl2 Bodenkörper. Das 7‐ und 6‐Hydrat sind hier in bezug auf MgB6O10 · 5 H2O unter der Mutterlauge metastabil. Bei der Entwässerung liefert lediglich das 7‐Hydrat nach Verlust von 2 Mol H2O eine definierte Hydratstu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…At all the reaction temperatures and reaction times, Mcallisterite is observed to be the major phase, whereas admontite is major only at 70 ∘ C and 90 min. These results are also consistent with the results reported in Derun et al [26] and Lehmann and Rietz [29], where the authors synthesised different types of magnesium borates (MgB 6 O 10 ⋅ H 2 O ( = 5, 6, 7, and 7.5)).…”
Section: Syntheses Xrd Resultssupporting
confidence: 92%
“…At all the reaction temperatures and reaction times, Mcallisterite is observed to be the major phase, whereas admontite is major only at 70 ∘ C and 90 min. These results are also consistent with the results reported in Derun et al [26] and Lehmann and Rietz [29], where the authors synthesised different types of magnesium borates (MgB 6 O 10 ⋅ H 2 O ( = 5, 6, 7, and 7.5)).…”
Section: Syntheses Xrd Resultssupporting
confidence: 92%
“…(2,7) All the reagents were analytical grade (Beijing Chemical Factory, P.R.C. The solid was separated, washed thoroughly with distilled water, and then with alcohol and ether.…”
Section: Methodsmentioning
confidence: 99%
“…Aksaite, (1,2) MgB 6 O 10 · 5H 2 O, is a magnesium borate mineral with a structural formula of MgB 6 O 7 (OH) 6 · 2H 2 O and is found in several places in the world. Until now, there have been no reports on the thermodynamic properties of aksaite.…”
Section: Introductionmentioning
confidence: 99%
“…On the base of literatures [10,11], Jia et al [12] reported a modified synthesized method of aksaite (MgO•3B 2 O 3 •5H 2 O). A brief procedure was to use MgO, which was obtained by thermal decomposition of Mg(OH) 2 •4MgCO 3 •6H 2 O in an electric furnace at T=873 K for about 3 h, H 3 BO 3 , MgCl 2 •6H 2 O, and H 2 O (mass ratio= 1: 9.3: 50: 12.5) were transferred to a flask with a reflux condenser at the boiling temperature of 395.15 K and became a clear solution.…”
Section: Principals Of Synthesis Of Magnesium Boratesmentioning
confidence: 99%
“…The thermodynamic properties of magnesium borates mentioned were given in Table 2. 9,10,13]. [17] reported the thermodynamic properties of the aqueous ternary system (MgB 4 O 7 -MgSO 4 -H 2 O) at 298.15 K using isopiestic method, and qualified based on Pitzer ion-interaction model.…”
Section: Magnesium Boratesmentioning
confidence: 99%